2013
DOI: 10.5586/am.2013.017
|View full text |Cite
|
Sign up to set email alerts
|

Fungi of the genus Trichosporon isolated from the skin in hospitalized patients

Abstract: Fungi of the genus Trichosporon are widespread in the biosphere and are a frequent component of the skin mycobiota. They are opportunistic organisms that adopt a commensal lifestyle on the skin in healthy humans but can cause pathological changes (trichosporonosis) of various intensity and range in immunocompromised persons. The species recorded in our study (T. asahii, T. capitatum, T. cutaneum, T. inkin, T. pullulans) are potential anthropopathogens. T. asahii, T. cutaneum and T. inkin are classed as BSL-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Yeast‐like fungi may be asymptomatically present in the oral mucosa in 1/3 of the human population of different age groups and on the skin and its adnexa . According to Findley et al , a specific “map” of their distribution can be compiled.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast‐like fungi may be asymptomatically present in the oral mucosa in 1/3 of the human population of different age groups and on the skin and its adnexa . According to Findley et al , a specific “map” of their distribution can be compiled.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that yeast belonging to Trichosporon could cause superficial skin infections upon contacts [23]. However, T. cutaneum is still suitable for many biological wastewater treatments without contact of human [24].…”
Section: Comparison Of Fermentation With Other Oleaginous Microorganimentioning
confidence: 99%
“…In the latter case, the differences were smaller or did not exist. The examples include: the identical number of fungal species in spring and autumn in the beaks of young birds (15), and in the cloaca of adult individuals (10). Interestingly, the diversity in the number and taxonomy of fungi in the beak of all birds was higher in autumn, and the number of species in the cloaca of young birds doubled, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Fungi from the Trichosporon genus show an increasing range of viable host organs in humans with T. cutaneum being increasingly frequently isolated from the respiratory tract, digestive tract, and skin, and T. asteroides being responsible for superficial infections (10). However, C. neoformans is a fungus that is thought to be the most dangerous to humans, especially to children.…”
Section: Discussionmentioning
confidence: 99%